2013
DOI: 10.5846/stxb201207311087
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maize‖peanut intercropping on photosynthetic characters and yield forming of intercropped maize

Abstract: Intercropping is a popular cropping system in high鄄yielding production of food and feed in the world, which is more productive than monocropping because of the intensive utilization of natural resources, such as sunlight, heat, water and fertilizer. As a component crop in most intercropping systems, maize can be intercropped with a variety of crops, such as common bean, faba bean, soybean and peanut, showing an important role, and an obvious intercropping yield advantage. Maize 椰 peanut intercropping as an imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The yield-increasing benefits of maize in interand mixed cropping have been discussed in detail. In terms of morphological structure, the maize inter-and mixed cropping system facilitated the formation of a three-dimensional canopy structure and different intercropping row ratios and planting densities brought differences in light distribution, which improved the ventilation and light transmittance and increased CO 2 concentration in the growth space [53][54][55]. In terms of physiology, inter-and mixed cropping mode increased the chlorophyll content, leaf area index, and photosynthetic rate of maize [19,22].…”
Section: Discussionmentioning
confidence: 99%
“…The yield-increasing benefits of maize in interand mixed cropping have been discussed in detail. In terms of morphological structure, the maize inter-and mixed cropping system facilitated the formation of a three-dimensional canopy structure and different intercropping row ratios and planting densities brought differences in light distribution, which improved the ventilation and light transmittance and increased CO 2 concentration in the growth space [53][54][55]. In terms of physiology, inter-and mixed cropping mode increased the chlorophyll content, leaf area index, and photosynthetic rate of maize [19,22].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the increase of stomatal conductance promoted the degree of CO 2 acquisition and transportation (Figure 3b), thereby accelerating the production and accumulation of organic matter in plants [44]. At the same time, the maximum carboxylation rate, which is an important parameter for characterizing photosynthetic capacity of plants, also increased (Figure 3b), indicating that NO 2 fumigation increased Rubisco activity of mulberry leaves, thereby enhancing the fixation ability of CO 2 [45] . Moreover, the dark respiration rate was significantly increased (Figure 3d), indicating that its fumigated leaves consumed excess light energy through respiration to protect the photosynthetic system and increase the photosynthetic rate.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, intercropping with cowpea (Vigna sinensis L.) in India enhances the yield of the current crop and boosts the yield of subsequent winter wheat [16]. In the North China Plain, our previous research has shown that intercropping maize and peanut (M||P) offers significant yield advantages, attributed to positive aboveground and belowground interspecific interactions influencing crop plant growth [17,18]. These mechanisms may involve enhancing iron and nitrogen reciprocity between maize and peanut [19] and weak light absorption and utilization by peanut [20] along with strong light utilization by maize [17].…”
Section: Introductionmentioning
confidence: 99%
“…In the North China Plain, our previous research has shown that intercropping maize and peanut (M||P) offers significant yield advantages, attributed to positive aboveground and belowground interspecific interactions influencing crop plant growth [17,18]. These mechanisms may involve enhancing iron and nitrogen reciprocity between maize and peanut [19] and weak light absorption and utilization by peanut [20] along with strong light utilization by maize [17]. Feng et al showed that the worldwide average LER of maize intercropping with peanut was 1.31 ± 0.03 through a global meta-analysis of 36 studies [21].…”
Section: Introductionmentioning
confidence: 99%